Cannabidiol Psychoactivity: A Perspective on Claims of US Patent 6630507 - Dawson, David A (Journal of Medical Biomedical and Applied Sciences, 2019)
The Department of Health and Human Services owns US Patent 6630507 which states that cannabinoids are powerfulantioxidants and have the potential to treat myriad ischemic, age-related, inflammatory, and auto-immune disorders. Thepatent claims cannabinoids are also a natural neuroprotectant which could help treat neurological damage caused bystroke and trauma, as well as other neurological disorders like Alzheimer’s, Parkinson’s Disease, and Multiple Sclerosis.This perspective paper assesses the properties and usefulness of the patented cannabinoid.